Solución pacífica de conflictos en el aula a través de la pedagogía del cuidado en los estudiantes de la post primaria barrancón de la Institución Educativa Departamental Eduardo Santos del municipio de Yacopí, Cundinamarca (2017)
Educate for coexistence in classroom of schools, students use the necessary citizen skills in the assertive and peaceful solution of the conflicts that arise in the daily life of students. This research aims to answer the question How to promote a healthy school life, by achieving peaceful solutions to transform the daily life of the students of the Barrancón Post primary of the I.E.D. Eduardo Santos of the Municipality of Yacopí, Cundinamarca? To this end, it addresses the pedagogy of care as the approach in the peaceful solution of conflicts in the classroom, pedagogical strategies are developed that orient new learning environments; To knowledge, experimental, reflective and critical; To the different forms of attention and handling of the conflicts as well as the different criteria that must be taken into account in the decision making...